2008
DOI: 10.1002/ejoc.200800045
|View full text |Cite
|
Sign up to set email alerts
|

Heterocyclic Quinol‐Type Fluorophores: Solid‐State Fluorescence Change in Crystals of Benzo[b]naphtho[1,2‐d]furan‐6‐one‐Type Fluorophore upon Inclusion of Organic Solvent Molecules

Abstract: The crystals of novel benzo [b]naphtho [1,2-d]furan-6-one-type fluorophores (1) exhibit sensitive colour and fluorescence change upon enclathration of organic solvent molecules. The crystal of the fluorophore 1b (R = Bu) exhibits fluorescence decrease upon inclusion of cyclohexane, however, the crystal of the fluorophore 1c (R = Ph) exhibits a drastic fluorescence enhancement upon inclusion of chloroform. To elucidate the enclathrated guest effects on the photophysical properties of the crystals, the X-ray cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Strong intermolecular π-π interactions between the fluorophores induce a large redshift in the absorption and fluorescence maxima and an intense fluorescence quenching in the solid state. [2,3,5,9] However, the solidstate fluorescence intensity of 2·ethanol is weaker than that of 2·ethyl acetate. It is considered that the continuous intermolecular hydrogen bonding ranging alternately host and www.eurjoc.orgguest (···H···G···H···) was only observed in 2·ethanol, which is a principal factor leading to fluorescence quenching in the solid state.…”
Section: Relation Between Solid-state Fluorescence Properties and X-rmentioning
confidence: 81%
See 1 more Smart Citation
“…Strong intermolecular π-π interactions between the fluorophores induce a large redshift in the absorption and fluorescence maxima and an intense fluorescence quenching in the solid state. [2,3,5,9] However, the solidstate fluorescence intensity of 2·ethanol is weaker than that of 2·ethyl acetate. It is considered that the continuous intermolecular hydrogen bonding ranging alternately host and www.eurjoc.orgguest (···H···G···H···) was only observed in 2·ethanol, which is a principal factor leading to fluorescence quenching in the solid state.…”
Section: Relation Between Solid-state Fluorescence Properties and X-rmentioning
confidence: 81%
“…In our previous works, we reported novel benzofurano [3,2-b]naphthoquinol-type, [5] imidazo [5,4-a]anthraquinol-type, [8] 5-hydroxy-5-substituent-benzo [b]naphtho[1,2-d]-furan-6-one-type [9] and phenanthro [9,10-d]imidazoletype [10] fluorescent hosts, whose crystals exhibit a dramatic fluorescence enhancement upon inclusion of various amines, organic solvents and carboxylic acids. In particular, imidazo [5,4-a]anthraquinol-type fluorophores, in which two tautomeric forms (A and B) are possible for the imidazole ring, can include various kinds of organic solvent molecules in the crystalline state by changing the tautomeric form of the imidazole ring.…”
Section: Introductionmentioning
confidence: 99%
“…These long-range host-host interactions based on continuous intermolecular hydrogen bonds and π-π interactions would cause a strong fluorescence quenching in the guest-free crystal. [5][6][7][8]11] In contrast, in the case of the carboxylic acid inclusion crystals, such direct intermolecular hydrogen bonding between host molecules is not found. Instead, the carboxylic acid inclusion crystals, except those of 1·[HOOC(CH 2 ) 8 -COOH] 2 , are made up of a hydrogen-bonded cluster unit composed of two imidazole hosts and four carboxylic acid guests ( Figures 7, 8 and 9).…”
Section: Relation Between Solid-state Fluorescence Properties and X-rmentioning
confidence: 94%
“…[1][2][3][4] Several types of fluorescent hosts exhibit fluorescence enhancement behaviour with a blueshift in the fluorescence wavelength maximum upon inclusion of various organic solvent molecules. [5][6][7][8][9][10][11] From comparison of the X-ray crystal structures of the guest-free and several clathrate compounds, it was concluded that the changes in molecular arrangement by the formation of CH-π interactions and the destructions of π-π interactions and the intermolecular hydrogen bonds binding fluorophores by the enclathrated guest molecules are the main reason for the guest-dependent fluorescence enhancement and the blueshift in the fluorescence maximum of the crystals. In contrast, we reported that a new phenanthro [9,10-d]imidazole-type fluorescent host, [12] 2-[4-(diethylamino)phenyl]-1H-phenanthro [9,10-d]imidazole (1; Scheme 1), whose crys-cent intensity changes.…”
Section: Introductionmentioning
confidence: 99%
“…Solid state organic luminescent materials particularly with tunable luminescence are of great interest in recent years, because of their applications in the field of optoelectronic devices, including organic electroluminescence (EL), light‐emitting diodes (LEDs), and optical sensors 1–8. Organic molecules, for example, π‐conjugated molecules show high luminescence in dilute solution9–15 but become weakly luminescent in the solid state due to the formation of less emissive species such as excimers that restrict the applications of these molecules in high density optical systems 16, 17. Strategies, such as the introduction of bulky substituents or the synthesis of propeller‐shaped luminescent molecules which prevent close‐packing in the solid state, have successfully lead to organic molecules that luminescence in the solid state 18–22.…”
Section: Introductionmentioning
confidence: 99%